Interplay of the Quality of Ciprofloxacin and Antibiotic Resistance in Developing Countries - Sharma, Deepali; Patel, Rahul P.; Zaidi, Syed Tabish R.; Sarker, Md. Moklesur Rahman; Lean, Qi Ying; Ming, Long C. (Frontiers in Pharmacology, 2017)
Ciprofloxacin, a second-generation broad spectrum fluoroquinolone, is active against both Gram-positive and Gram-negative bacteria. Ciprofloxacin has a high oral bioavailability and a large volume of distribution. It is used for the treatment of a wide range of infections including urinary tract infections caused by susceptible bacteria. However, the substandard and spurious quality of oral ciprofloxacin formulations in the developing countries has been thought to have contributed towards increased risk of treatment failure and bacterial resistance. Therefore, quality control and bioequivalence studies of the commercially available oral ciprofloxacin formulations should be monitored. Appropriate actions should be taken against offending manufacturers in order to prevent the sale of substandard medications, especially the spurious oral ciprofloxacin products.